Towards a Promising Nanoformulation for the Treatment of Parkinson’s Disease - Abdel Dayem, Dania (AUC Knowledge Fountain, 2025)
Parkinson’s Disease (PD) is a growing global health concern; it is the fastest-growing neurodegenerative disease and is a leading cause of disability. Moreover, currently available treatments for PD are unable to restore damaged neurons nor are they able to reduce disease progression, but rather they provide short-term relief of symptoms and at later stages, these treatments become increasingly ineffective. Accordingly, research has aimed to explore potential therapies that may help halt or slow down the disease progression. One of those potential treatments is a c-Abl inhibitor, nilotinib, however, its clinical effectiveness was limited in PD patients. One possible explanation is linked to its poor bioavailability and brain penetration capacity. In fact, reaching and maintaining the minimum required therapeutic concentration of nilotinib (i.e.,150 nM) in the brains of patients was a challenge. Accordingly, this study focused on developing nanostructured lipid carriers (NLCs) to encapsulate nilotinib, an insoluble “brick dust” drug. By conjugating glutathione (GSH) and lactoferrin (Lf) to the NLC surface via a maleimide linker, this work aimed to enhance brain delivery and therapeutic efficacy of nilotinib. It was found that the dual-ligand functionalized NLC formulation (NLC-G-Lf) demonstrated exceptional improvements in a preclinical acute-MPTP PD mouse model. Key characteristics of the NLC-G-Lf formulation included a hydrodynamic size of 260.3 nm and a zeta potential of -15.6 mV. The formulation exhibited excellent behavioral outcomes compared to nilotinib in PEG-400 vehicle; the NLC-G-Lf formulation led to the most significant improvement in motor function, with test performances rivaling those of the naive control in the pole test. Pharmacokinetic studies further reinforced these findings, revealing that NLC-G-Lf achieved the highest systemic drug exposure, with a 6h AUC of 70,777 nM.h which is approximately 3.5 times that of the nilotinib in vehicle-treated group, suggesting a significantly improved systemic bioavailability. Interestingly, formulations containing only one ligand (either GSH or Lf) resulted in lower systemic drug exposure, likely due to increased clearance. Accordingly, there seems to be a synergy between glutathione and lactoferrin playing a crucial role in the dual-ligands formula’s success. It is predicted that the unique reaction occurring between four of Lf's cysteines with glutathione, leading to the conversion of the nascent Lf protein to a folded tertiary structure, seems to provide additional stability and protection of the NLCs. By using, nanotechnology and ligand-based targeting, this work highlights a promising strategy to improve the therapeutic effect of low solubility “brick dust” drugs such as nilotinib.